Lower respiratory tract infections in rheumatic diseases - B. S. Belov; D. V. Bukhanova; G. M. Tarasova (Современная ревматология)
Lower respiratory tract infections occupy a leading place in patients with rheumatic diseases (RDs). Pneumococcus (S. pneumoniae) remains the most common causative pathogen of pneumonias in  both the general population and patients with RDs. This review gives the frequency and risk factors of pneumonias in different RDs. It  presents the main clinical characteristics and approaches to treating  and preventing pneumonias due to various (including opportunistic)  infections. The problem of pneumonias is very relevant in patients  with RDs and it has been simultaneously extremely little developed – there are single publications on this problem are available in the  Russian literature. There is a need for further investigations of its  various aspects (including the efficiency of and safety of vaccination) in Russia within the uniform science program, which will make it  possible to develop clinical guidelines for the management of these patients.